2006
DOI: 10.1051/0004-6361:20054626
|View full text |Cite
|
Sign up to set email alerts
|

Are $\mathsf{^{44}}$Ti-producing supernovae exceptional?

Abstract: According to standard models supernovae produce radioactive 44 Ti, which should be visible in gamma-rays following decay to 44 Ca for a few centuries. 44 Ti production is believed to be the source of cosmic 44 Ca, whose abundance is well established. Yet, gamma-ray telescopes have not seen the expected young remnants of core collapse events. The 44 Ti mean life of τ 89 y and the Galactic supernova rate of 3/100 y imply several detectable 44 Ti gamma-ray sources, but only one is clearly seen, the 340-year-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 115 publications
(199 reference statements)
5
98
0
Order By: Relevance
“…These values agree with the compilation of observational constraints done in Martin et al (2010) and with the recently-estimated range for G1.9+0.3 (Borkowski et al 2010). Overall, this corresponds to a mean Galactic 44 Ti production rate of 4.2 ×10 −6 M yr −1 , roughly consistent with the estimate of 5.5 × 10 −6 M yr −1 by The et al (2006) based on the present-day solar 44 Ca abundance and a Galactic chemical evolution model. This 44 Ti production rate can be translated into a positron production rate by applying a factor 0.94 for the β + -decay branching ratio of the decay chain and using an escape fraction of 100%.…”
Section: The 44 Ti Radio-isotopesupporting
confidence: 90%
See 1 more Smart Citation
“…These values agree with the compilation of observational constraints done in Martin et al (2010) and with the recently-estimated range for G1.9+0.3 (Borkowski et al 2010). Overall, this corresponds to a mean Galactic 44 Ti production rate of 4.2 ×10 −6 M yr −1 , roughly consistent with the estimate of 5.5 × 10 −6 M yr −1 by The et al (2006) based on the present-day solar 44 Ca abundance and a Galactic chemical evolution model. This 44 Ti production rate can be translated into a positron production rate by applying a factor 0.94 for the β + -decay branching ratio of the decay chain and using an escape fraction of 100%.…”
Section: The 44 Ti Radio-isotopesupporting
confidence: 90%
“…The 56 Ni isotope is synthesised by explosive Si-burning deep in the stellar ejecta during core-collapse and thermonuclear 7 In The et al (2006), the authors found a ∼2 times larger uncertainty range for the Galactic 44 Ti production rate due to unknown parameters in the Galactic chemical evolution model; they also note that the entire range may be shifted to lower values if there is a nucleosynthesis channel to produce 44 Ca directly.…”
Section: The 56 Ni Radio-isotopementioning
confidence: 99%
“…The characteristics of 44 Ti emission from the Cas A supernova remnant and candidate sources in the Galaxy show that nucleosynthesis in core-collapse supernovae occurs under a diversity of environmental conditions, which result from substantial deviations from spherical symmetry in these explosions [127]. Exploitation of gamma-rays from the 56 Ni decay chain which is responsible for supernova light still awaits a sufficiently-nearby supernova of type Ia [49]; the independent information carried by gamma-rays from this decay chain could help to understand details of explosion physics, which happens in the dense and dynamic initial phase of the exploding star that is otherwise occulted to observations.…”
Section: Discussionmentioning
confidence: 99%
“…Both the COMPTEL and INTEGRAL suverys fail to detect the expected numbers of 44 Ti sources. In spite of the low number of events involved, this is a significant observation [126,108]. Thus, also from the rate of 44 Ti emitting core-collapse supernovae, it seems that object to object variations must be large, and 44 Ti ejection non-typical, probably much larger than current models predict in case they do happen.…”
Section: The Iron and Velocity Distribution In Cassiopeia Amentioning
confidence: 91%
See 1 more Smart Citation